Investigation Tourism Development on Geopark Caldera Toba with Spatial Autocorrelation Approach - Damanik, Darwin; Sirojuzilam; Syafii, M.; Ruslan, Dede (Journal of Ecohumanism, 2024)
This study analyzes the spatial linkage of economic growth in 8 (eight) Lake Toba Districts with a time period of 2010 - 2022. This study focuses on hypothesis testing that examines the influence of the determinants of regional economic growth by considering spatial aspects and also analyzes the convergence of economic growth with respect to spatial aspects. The estimation method is carried out using the spatial panel data estimation method, namely the dynamic spatial Durbin models (SDM) method. In the estimation of the research using the help of Stata and Geoda software. Determinants of economic growth from other districts (there is spatial spillover); Determinants of economic growth from the district itself include physical capital investment, human capital investment, population, tourism sector contribution, road infrastructure, and tourism and cultural spending have a significant impact on economic growth in the eight districts of the Lake Toba region of North Sumatra Province, and Determinants of economic growth from other districts (there is positive spatial spillover) on regional economic growth in the eight districts of the Lake Toba region of North Sumatra Province include real per capita income of other districts, physical capital investment of other districts, human capital investment of other districts, population growth of other districts, contribution of tourism sector of other districts, and road infrastructure of other districts.